Experimental Evaluation of Three Different Humidity Conditions to Physical and Mechanical Properties of Three Different Mixtures of Unfired Soil Bricks - Purnomo, Heru; Arini, Srikandi Wahyu (UI Scholars Hub, 2019)
Unfired brick is considered as a more environmentally friendly material than fired brick. It has lower mechanical properties than that of fired brick where humidity influences both bricks. Physical and mechanical properties of unfired bricks made of three kinds of mixtures were studied experimentally under three humidity conditions. The first kind of unfired brick was made only with soil and water while the second type was made of a mixture of soil, water and lime, and the third type was a mixture of soil, water, lime and uniform treated coir where 4% of lime mass was substituted with coir mass. Physical properties evaluation consisted of water content, absorption, volume shrinkage and density of those unfired bricks. Some variations occur in the third type of unfired bricks physical test results, where in general in more humid conditions there are tendency to have higher density, higher absorption, higher water content and less volume shrinkage compared to two other types of unfired bricks. Mechanical properties are evaluated by its modulus of rupture, compressive strength and modulus of elasticity. It is found that the addition of 4% treated 2.5 cm coir gives better mechanical properties in humid conditions compared to others types of unfired bricks.